Reinterpreting ‘God’s Time’ in Agrarian Conflict: Kairos Theology and Christian Education in Indonesia - Adi, Raden Bima (Evangelikal: Jurnal Teologi Injili dan Pembinaan Warga Jemaat, 2026)
This study addressed the theological and sociopolitical gap in Indonesia's response to agrarian and ecological crises. It aimed to reinterpret the concept of 'God's time' through a Kairos lens, linking it to Christian educational praxis and eco-theological thought. This study focused on Indonesian regions facing intense land conflict and ecological degradation, particularly those involving indigenous communities. Using a qualitative theological design, this study employed a critical textual analysis of Kairos documents, an ethnographic content analysis of local cultural practices, and a literature review of Christian education and contextual eco-theology. Data triangulation was achieved through document comparison and thematic coding. The results showed that the phrase 'God's time' was often used passively in Christian discourse, frequently serving institutional and political interests instead of inspiring prophetic action. The study concluded that Christian education, when grounded in local wisdom and Kairos theology, has transformative potential to reframe time theologically and promote ecological solidarity. As a practical contribution, this study proposed a contextual framework for prophetic theological education in Indonesia, including a curricular model that integrates environmental justice, indigenous wisdom, and critical solidarity as core components of Christian educational praxis.